Acute pancreatitis: a study of urine trypsinogen-2 measurement as a screening test - Nittala, Rigved; Basheer, O. T. M.; Sasi, M. P. (International Journal of Research in Medical Sciences, 2017)
Background: Usefulness of urine trypsinogen-2 as screening test for acute pancreatitis in Indian population. Methods:We prospectively compared the urinary trypsinogen-2 dipstick test and serum amylase assays in 100 consecutive patients with acute abdominal pain at the emergency department. Urine samples were obtained on admission and tested for the dipstick. The diagnosis of acute pancreatitis was made on the basis of a typical clinical picture and serum amylase at least more than threefold the upper reference limit (300 IU) and/or radiological evidence (Abdominal X ray/ultrasonography/contrast enhanced CT). Results: 1. Urine trypsinogen-2 dipstick test was having 100% sensitivity and 85.71% specificity in diagnosing acute pancreatitis in Indian population. 2. Serum amylase was having 61.36% sensitivity and 78.57% specificity in diagnosing acute pancreatitis. 3. Sensitivity and specificity of urine trypsinogen-2 dipstick test is more than that of serum amylase in diagnosing acute pancreatitis which is statistically proved to be significant (P <0.05). Conclusion:Detection of trypsinogen-2 in urine is a simple office test in diagnosing acute pancreatitis in emergency department. As the sensitivity and specificity are high, detection of urine trypsinogen-2 in urine can be used as a screening test, which will definitely help in early diagnosis and prompt treatment of acute pancreatitis.